Comparative study of outcomes in patients where pneumoperitoneum is created by Veress needle versus open method in laparoscopic surgeries - Thakore, Digpal; RAY, M. S.; Modi, Naresh; Panchal, Brinda; Raval, Aditya; Patel, Vishal (International Surgery Journal, 2023)
Background: The establishment of pneumoperitoneum is the inevitable first step in laparoscopic surgery as it increases the distance between the anterior abdominal wall and intra-abdominal viscera, thus creating a working space. Methods: This prospective study was conducted on 50 patients. Patients were randomly divided into two groups, in first group, pneumoperitoneum is created by Veress needle and in second group, pneumoperitoneum is created by open method. Results: The open method takes less time to create pneumoperitoneum while leads to statistically significant more gas leaks as compared to the closed method. Conclusions: The open technique is almost equal to closed technique or Veress technique in terms of the time taken to complete the operation and major and minor complications because there was no statistically significant difference in the frequency of these parameters between the two techniques. The open method takes less time to create pneumoperitoneum while leads to statistically significant more gas leaks as compared to the closed method.